Patriotyzm w polityce - pojęcie tylko historyczne? - Paweł Kuglarz (Jesuit University Ignatianum in Krakow, 2017)
The article takes up the issue of patriotism understood as the social-political attitude based on the principles of love and friendship towards the homeland, unity and solidarity with one's own nation, the sense of social bond and cultural community with compatriots. The notion of patriotism has changed a lot through the years. The author depicts historical development of this concept since medieval times up to the present day. At present, patriotism essentially means work at the foundations, work for one's own, but, at the same time, for the whole society. The issue of patriotism today requires new consideration, especially in the prospect of the processes of economic and cultural globalisation. If, in the past, patriotism was developing in the perspective of the whole nation, or state, today, it rather relates to small local communities, where people organise according to their private needs and interests, where tradition as well as national and local culture are cultivated. The nation's position in the world can be measured by the value of culture and its powers of radiation. Contemporary patriotism has to go hand in hand with conviction that each homeland constitutes a part of a huge world homeland. Therefore, an attitude of openness to others is required as well as awareness that the increase of the ethical level of interpersonal elations takes place in the spiritual and cultural revival of local traditions.